Pengaruh Leverage, Return on Assets, dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia - Sitopu, Chintya Lauren; Situngkir, Anggiat; Napitupulu, Ilham Hidayah; Syahputra, Rizki (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to empirically analyze the effect of leverage, return on assets, and firm size on tax avoidance among LQ45 companies listed on the Indonesia Stock Exchange during the 2019–2024 period. The research population consists of 45 companies, with purposive sampling resulting in 6 firms as the sample, based on the following criteria: consistently included in the LQ45 index throughout the study period, publishing complete annual financial statements, and providing relevant data for calculating the research variables. Data collection was carried out using documentation of annual financial statements obtained from the official website of the Indonesia Stock Exchange. Data analysis was conducted using a quantitative approach through multiple linear regression with the aid of SPSS version 25, which included descriptive statistics, classical assumption tests, regression analysis, and hypothesis testing. The findings indicate that leverage and return on assets do not have a significant effect on tax avoidance, while firm size has a significant effect on tax avoidance among LQ45 companies listed on the Indonesia Stock Exchange for the 2019–2024 period. These results provide implications for tax authorities to enhance monitoring of large companies, as well as for investors and creditors as a consideration in decision-making. The limitation of this study lies in the small sample size and relatively short observation period.